Role of Leadership and Learning Environment in Influencing Learning Achievement Level of Students: A Study of Gamo Gofa Zone of Ethiopia - Ambaw, Betta Tsemato; Meher, Rajkishor (International Journal of Criminology and Sociology, 2019)
The purpose of this study was to examine the level of influence of leadership and learning environment on students’ academic achievement. The study employed survey design, quantitative method and simple random sampling technique. The data were analyzed using frequency distribution and independent samples t-test. The findings indicated that while both leadership and learning environment had a positive influence on the level of the students’ learning achievement, leadership tended to have a greater influence than learning environment in the study area. Thus, the primary school principals in Gamo Gofa Zone need to keep on applying appropriate leadership styles besides establishing conducive learning environment in their respective schools; moreover, rigorous research supported by causal comparative model has to be conducted on the research problem so that it might contribute to alleviating the problem